2019
DOI: 10.18332/tid/110007
|View full text |Cite
|
Sign up to set email alerts
|

Implementing smoke-free policies in low- and middle-income countries: A brief review and research agenda

Abstract: INTRODUCTIONSome low- and middle-income countries (LMICs) struggle to implement smoke-free policies. We sought to review the academic and gray literature, and propose a research agenda to improve implementation of smoke-free policies and make them more effective in LMICs.METHODSWe reviewed 10 databases for variations of (‘implementation’ /‘enforcement’ /‘compliance’) and (‘smoke-free’ /‘ban’ /‘restriction’) and (‘tobacco’ /‘smoking’). We also reviewed cited sources and the gray literature including non-governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 63 publications
3
51
0
2
Order By: Relevance
“…There is no riskfree level of SHS and even brief/minimal exposure can cause immediate harm 2,33 . Non-compliance with smoke-free laws among hospitality venues has also been found in other LMICs including those of Africa 21,31 . The results and outcome of this research serve as a basis for discussions on the need to develop specific policies to protect consumers and employees of such premises, and also implement enforcement measures to improve compliance.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There is no riskfree level of SHS and even brief/minimal exposure can cause immediate harm 2,33 . Non-compliance with smoke-free laws among hospitality venues has also been found in other LMICs including those of Africa 21,31 . The results and outcome of this research serve as a basis for discussions on the need to develop specific policies to protect consumers and employees of such premises, and also implement enforcement measures to improve compliance.…”
Section: Discussionmentioning
confidence: 78%
“…Lessons could be learnt from Seychelles, a similar country in Africa, where the compliance to smoke-free laws was impressively high in bars and restaurants after only nine months of the enactment of the smoke-free law 30 . Contributing factors for the situation in Seychelles included a smaller country size (thus requiring fewer resources for implementation), high awareness and knowledge of the smoking ban among hospitality staff, training of hospitality staff on how to enforce the ban, and active enforcement of the ban by venue workers 31 .…”
Section: Discussionmentioning
confidence: 99%
“…From eligible studies, we will extract the following items: (1) the first author's name, (2) his or her affiliation, (3) publication year, (4) type of publication (journal, book, dissertation, etc), (5) access information (URL or doi), (6) study design, (7) observational period (the beginning and end dates), (8) exact places covered by the policy, (9) whether the policy covers outdoor or indoor places, (10) whether the policy covers public or (semi)private, places, (11) timing of policy, (12) institution/government that initiated the policy, (13) country/location where the policy had been implemented, (14) compliance with the policy, (15) enforcement of the policy, (16) eligibility criteria for inclusion, (17) description of control group(s), (18) population at risk, (19) number of participants/events, (20) control and treatment group size, (21) characteristics of the population and the treatment groups (eg, age, gender and socioeconomic status), (22) data source(s) used for the study, (23) definition(s) of outcome measure(s), (24) controlled confounders (if applicable), (25) applied statistical techniques to draw inference, (26) number of clusters (if applicable), (27) cluster size (if applicable), (28) whether the results were adjusted for clustering (if clustered study), (29) whether the intraclass correlation coefficient is reported and what it is (if clustered study), (30) the number of drop-outs/ missing values, (31) techniques for handling missing values, (32) preintervention population at risk(n)/ events(n)/rates (%) of outcome variable(s), (33) postintervention population at risk(n)/events(n) rates (%) of outcome variable(s), (34) association between smoke-free policy and outcome(s) (coefficients, CIs and p values), (35) any unintended effects (eg, TSE displacement), (36) proportion of children exposed to TSE in the location covered by the smoke-free policy, before and after the implementation of the policy, (37) risk ratios (RRs) of respiratory disease for different levels of TSE according to specific locations covered by the smoke-free policy, (38) bias assessment (see section 'Risk of bias assessment'), (39) elements supporting causal inference (see section 'Elements supporting causal inference'), (40) any conflict of interest reported by the authors and (41) the funding source(s).…”
Section: Data Itemsmentioning
confidence: 99%
“…[4][5][6][7][8] Although in low-income and middle-income countries high background air pollution, poor economic conditions and low awareness of tobacco-related harm might obscure the positive effects of smoke-free legislation, evidence suggests that smokefree policies can have a similarly positive impact in these countries as in high-income countries. [9][10][11] As a result, smoke-free legislation is increasingly recognised as an important policy tool to protect children from the adverse health effects of TSE (eg, incorporated in Sustainable Development Goals 3.2, 3.4, 3.9 and 3.A that aim to improve health and well-being). 3 Recently, policies to provide additional protection of children to TSE beyond enclosed public places have been implemented in a number of places, both at a national and a subnational level.…”
Section: Introductionmentioning
confidence: 99%
“…In LMIC countries, the implementation should be performed together with measures to change smoker’s beliefs, social and cultural smoking norms, along with the increase of ground-level will to enforce policies. 10 , 11 Thus, exploration on factors related to compliance with smoke-free law in setting such as Indonesia should include an assessment of social norms. There are two type of social norms that should be taken into accounts in such study: descriptive norms and injunctive norms.…”
Section: Introductionmentioning
confidence: 99%